(3GdHjGf hGdJMUjd deG aj GdeSJNQLI ef GdJhLjg hGdJYdjds - (3eMeO Hf CMeO Hf CMeO Hf QTO GdeGdcj GdbQWHj GdCfOdSj, GdbGVj CHh GdhdjO (B( (3GdLO (B)(3, J (B520 (3g` s ((3CMeO Hf Ydi Hf CMeO GdUfgGLi s)
(3ChdgG (B:s
(3GdMeO ddg GdcHjQ GdeJYGd GdYRjR Gdegjef s
(3BNQgG (B:s
(3hGdaQb Hjf Cf jNdd eG GbJfi ef GdNeQ Ch eG jNeQ YfOg Je GdLRA GdJGSY ef GdLGeY ef cJGH GdHjGf hGdJMUjd hGdTQM hGdJhLjg Je LejY GdOjhGf s
(3HChdgG JMHjS dCHh GdMSf Ydi Hf CHj SYjO GdeQjfi Ydi NRGfI eOQSI YOhI GdCfOdSi HaGS SfI (B728s
(3cJHJ GdfSNI Ydi Qb ZRGds
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B228s
Keywords: (3Gdabg GdeGdcjs